The genetic landscape of familial congenital hydrocephalus. Issue 6 (June 2017) - Shaheen, Ranad; Sebai, Mohammed Adeeb; Patel, Nisha; Ewida, Nour; Kurdi, Wesam; Altweijri, Ikhlass; Sogaty, Sameera; Almardawi, Elham; Seidahmed, Mohammed Zain; Alnemri, Abdulrahman; Madirevula, Sateesh; Ibrahim, Niema; et al.
Abstract : Objective: Congenital hydrocephalus is an important birth defect, the genetics of which remains incompletely understood. To date, only 4 genes are known to cause Mendelian diseases in which congenital hydrocephalus is the main or sole clinical feature, 2 X‐linked ( L1CAM and AP1S2 ) and 2 autosomal recessive ( CCDC88C and MPDZ ). In this study, we aimed to determine the genetic etiology of familial congenital hydrocephalus with the assumption that these cases represent Mendelian forms of the disease. Methods: Exome sequencing combined, where applicable, with positional mapping. Results: We identified a likely causal mutation in the majority of these families (21 of 27, 78%), spanning 16 genes, none of which is X‐linked. Ciliopathies and dystroglycanopathies were the most common etiologies of congenital hydrocephalus in our cohort (19% and 26%, respectively). In 1 family with 4 affected members, we identified a homozygous truncating variant in EML1, which we propose as a novel cause of congenital hydrocephalus in addition to its suggested role in cortical malformation. Similarly, we show that recessive mutations in WDR81, previously linked to cerebellar ataxia, mental retardation, and disequilibrium syndrome 2, cause severe congenital hydrocephalus. Furthermore, we confirm the previously reported candidacy of MPDZ by presenting a phenotypic spectrum of congenital hydrocephalus associated with 5 recessive alleles. Interpretation: Our study highlights the importance of recessive mutations in familial congenital hydrocephalus and expands the locus heterogeneity of this condition. Ann Neurol 2017;81:890–897